Valproic Acid Initiates Transdifferentiation of the Human Ductal Adenocarcinoma Cell-line Panc-1 Into α-Like Cells - Petry, Sebastian Friedrich; Kandula, Naga Deepa; Günther, Stefan; Helker, Christian; Schagdarsurengin, Undraga; Linn, Thomas (Experimental and Clinical Endocrinology & Diabetes, 2022)
Non-mesenchymal pancreatic cells are a potential source for cell replacement. Their transdifferentiation can be achieved by triggering epigenetic remodeling through e. g. post-translational modification of histones. Valproic acid, a branched-chain saturated fatty acid with histone deacetylase inhibitor activity, was linked to the expression of key transcription factors of pancreatic lineage in epithelial cells and insulin transcription. However, the potential of valproic acid to cause cellular reprogramming is not fully understood. To shed further light on it we employed next-generation RNA sequencing, real-time PCR, and protein analyses by ELISA and western blot, to assess the impact of valproic acid on transcriptome and function of Panc-1-cells. Our results indicate that valproic acid has a significant impact on the cell cycle, cell adhesion, histone H3 acetylation, and metabolic pathways as well as the initiation of epithelial-mesenchymal transition through acetylation of histone H3 resulting in α-cell-like characteristics. We conclude that human epithelial pancreatic cells can be transdifferentiated into cells with endocrine properties through epigenetic regulation by valproic acid favoring an α-cell-like phenotype.
Keywords: pancreas; epigenetics; epithelial–mesenchymal transition